To the Maginot Line : the politics of French military preparation in the 1920's - Hughes, Judith M. (Harvard historical monographs, 2006)
The decision to fortify northeastern France has usually been considered a tragic mistake, an example of bad planning and missed opportunities. Not so, says Judith M. Hughes, who provides a convincing view of how France's military and political leaders tried to safeguard their nation and why they failed. As critic Michael Hurst writes in The American Historical Review, " The trends of French interwar history are deftly carried through onto these pages with an unobtrusive lucidity and persuasiveness."